2007
DOI: 10.1177/0956247807076784
|View full text |Cite
|
Sign up to set email alerts
|

São Paulo peri-urban dynamics: some social causes and environmental consequences

Abstract: This paper shows that the demographic growth of São Paulo's Metropolitan Area is very uneven. While the centre of the city is losing population, its farthest suburbs are growing quite fast. Furthermore, those fast growth areas are the poorest of the metropolitan area, with less infrastructure than other areas within the region and high levels of deforestation and informal land use. The objective of this paper is two-fold: fi rst, it explains the reasons for these intraurban dynamics by showing that the city is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 8 publications
0
15
0
6
Order By: Relevance
“…Environmental concern is highest among individuals experiencing poor local household environmental conditions. Other authors (Hunter, Strife, and Twine, 2010) also observed spatial variations in the relationship between objective problems and environmental concern, which likely result from different histories of urban development and variation in local biophysical characteristics (c.f., Pasternak, 2006; Torres, Alves, and Oliveira, 2007). Although the sign of the effects is similarly negative, the objective environmental condition measures are largely insignificant in the single-item analysis (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental concern is highest among individuals experiencing poor local household environmental conditions. Other authors (Hunter, Strife, and Twine, 2010) also observed spatial variations in the relationship between objective problems and environmental concern, which likely result from different histories of urban development and variation in local biophysical characteristics (c.f., Pasternak, 2006; Torres, Alves, and Oliveira, 2007). Although the sign of the effects is similarly negative, the objective environmental condition measures are largely insignificant in the single-item analysis (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively these areas encompass a region of about 82,000 ha and supply water to the São Paulo municipal district. These areas need urgent protection, as the rate of population growth is strongly positive in the forested areas that supply the water to these basins (and negative in denser urban areas), and the net loss of forest cover was a rate of 5.1% from 1991 to 2000 (Torres et al 2007). From 1989 to 1996, Guarapiranga alone lost 15% of its vegetation cover and suffered an urban growth rate of 50%, precipitating local water shortages and exorbitant costs associated with water treatment and purification (Schroeder 2008).…”
Section: Description and Backgroundmentioning
confidence: 99%
“…For example, Torres et al (2007) constructed a GIS integrating demographic census data, satellite remote sensing data, and other data sources to analyze the variability of demographic trends, real estate development, urban sprawl, deforestation, and urban infrastructure in the metropolitan region of São Paulo city, Brazil from the mid-1980s to 2003. These investigators showed that São Paulo's metropolitan core experienced both depopulation and growth in real estate investment while the city-region's poorest communities, located in the metropolitan periphery, expanded rapidly with relatively little formal private or public investment.…”
Section: Monitoring Mapping and Modeling Metropolitan Land Changementioning
confidence: 99%